Medical and social factors influencing the utilization of healthcare services among older adults in Israel during the COVID-19 lockdown - Shaked, Ohad; Korn, Liat; Shapiro, Yair; Zwilling, Moti; Zigdon, Avi (Frontiers in Public Health, 2023)
The corona virus disease 2019 (COVID-19) pandemic significantly impacted older people. However, most older communities focused on the medical issues. The aims of this study were to identify the medical and social factors linked with the usage of medical services during the COVID-19 lockdown in Israel.The study was conducted Over two periods of time from February to April in 2019 (P1), before the COVID-19 and from February to April in 2020 (P2), during the first lockdown. The study was conducted on people aged 65 and older in Israel. The variable statistics were analyzed using frequency tabulation, cross-tabulation frequencies, and t-tests. Two hierarchical logistic regressions were conducted over four steps for each period.The participants (n=102,303) comprised 64.5% female (65,946) and 35.5% male (36,357) (mean age 80.5, SD-7.46). It was found that participants who had not subscribed to the supportive community services were 7.47 times more likely to access medical services in P1 and 12.417 times more likely to access medical services during the lockdown. This variable was also found to be a strong predictor in the final model. The most significant variable for predicting the participants' needs during P2 was their previous needs in P1. Other social variables were living in assisted living home and living in community settlements. The presence of 12 diseases in this study did not predict service demand.Conclusions: Community support reduces medical service demands during disasters and provides services for older people. During pandemics, however, social services need to be expanded and made more easily accessible to older people.